Instant : Imaging. - Queensland Art Gallery, Brisbane (Brisbane : Queensland Art Gallery, 1991)
Davies, Mark ; To, Hiram ; Vidins, Edite ; Waller, John ; Hoffie, Pat ; Wolter, Adam ; Enright, Malcolm
Instant : Imaging, Queensland Art Gallery, Brisbane, 1991
boek